PENERAPAN CARA MENGHARDIK PADA PASIEN GANGGUAN PERSEPSI SENSORI : HALUSINASI PENDENGARAN DI RUANG TANJUNG BLUD RSU KOTA BANJAR - Asep Riyana; Siska Avidha Savitri; Heri Dj. Maulana (Jurnal Sehat Masada, 2023)
Hallucinations are a mental disorder caused by a change in sensory perception experienced by a person which can be caused by internal or external factors. The purpose of this scientific paper is to find out the patient's characteristics, describe the stages of implementing the rebuke method, and describe the decrease in signs and symptoms in patients with auditory hallucinations. The type of design is descriptive with a case study report. The results of the case studies from this scientific paper show that the two patients showed a decrease in the signs of hallucinations. as well as an increase in the ability to control hallucinations after being given rebuke.